Adenocarcinoma of intestinal type arising in mature cystic teratoma of ovary: A diagnostic dilemma. Issue 4 (6th February 2020) - Belaid, Imtinene; Khechine, Wiem; Ben Abdelkader, Atef; Bedioui, Ahlem; Ezzairi, Faten; Chabchoub, Imene; Boujnah, Ryma; Tlili, Taghrid; Hochlaf, Makrem; Ben Fatma, Leila; Mokni, Moncef; Ben Ahmed, Slim
Abstract: Adenocarcinomas of intestinal type arising in mature cystic teratoma of ovary (MCT) are extremely rare and remain a diagnostic dilemma because of its similarities with MCT. Serum tumor markers CEA and SCC and also MRI may help in the preoperative diagnosis. Pathologist experience helps in intraoperative diagnosis. Abstract : Adenocarcinomas of intestinal type arising in mature cystic teratoma of ovary (MCT) are extremely rare and remain a diagnostic dilemma because of its similarities with MCT. Serum tumor markers CEA and SCC and also MRI may help in the preoperative diagnosis. Pathologist experience helps in intraoperative diagnosis.